Optimalisasi Program Maintenance Dan Peningkatan Kinerja Wire Crane Dengan Mitigasi Risiko Proses Bongkar Muat Kapal M.V Hanglima - Raihan Gymnastiar Usman Usman; Supangat Supangat; Kuncowati Kuncowati (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
Wire cranes play a crucial role in the loading and unloading process on ships, especially in ports lacking land-based crane facilities. However, several problems were encountered on the MV Hanglima, including wire rope damage, overloading, and poor operational risk mitigation. This study aims to analyze wire crane maintenance, optimize its performance, and identify mitigation strategies for potential damage and accidents. The study employed a case study approach with thematic analysis, through observation, interviews, and documentation on board the MV Hanglima. The results indicate that the frequency of wire crane maintenance depends on the intensity of use and the working environment. Lifting loads exceeding safe limits can accelerate wire rope damage and reduce crane operational efficiency. Furthermore, lack of operator training, negligence in the use of personal protective equipment, and weak communication systems contribute to the increased risk of workplace accidents. Effective mitigation strategies include regular inspections, the use of load sensors, routine lubrication, and the implementation of emergency response standard operating procedures (SOPs). In conclusion, optimizing maintenance programs and integrated risk mitigation can improve wire crane performance and support the smooth and safe loading and unloading process on board.